(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
The forests of Chir pine (Pinus Roxburgii) encompass 97.4 thousand acres or 16.15 % of the total forest land of Uttrakhand, a state in India. According to Forest Department of India, Dehradun, a massive forest fire in 1995 engulfed 14.7 thousand acres of valuable forest area through 2,272 forest fire incidents in Uttrakhand, which resulted in the loss of crores of rupees and created various long-lasting ecological consequences. The fires damaged the fertile top layer of the soil and left a layer of pine needle litter that prevented rain water from being absorbed by the soil and contributed to early depletion of the groundwater cycle and stopped grass growth, thus depriving livestock of important food. So the question of what to do with these pine needles is an important one for forest and livestock. Regarding this problem, the German organization, Deutsche Gesellschaft für Internationale Zusammenarbeit, has been studying ways to use pine needles as a feedstock for downdraft gasifiers. If successful, the gasifier would provide incentive to collect the pine needles during dry months and improve the condition of the soil by allowing water to permeate top soils. Using chemical analysis, flue gas analysis, and combustion analysis, our paper analyzes the potential of pine needles as a substrate for gasification. We also argue that using pine needles in this way would alleviate carbon dioxide emissions due to forest fire. Average carbon dioxide emissions in forests that have an abundance of pine needles is 15.46%, but reduced to 12.8% when pine needles are used in a gasifier plant. DOI: http://dx.doi.org/10.3126/hn.v15i0.11299 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 15, 2014, July Page: 73-81